Analysis of the Need for Entrepreneurship Credentials Based on Local Potential in Vocational High Schools in Palangkaraya City - Nurbudiyani, Iin; Rahayu, Puput Puji; Septiani , Septiani (Reflection Journal, 2026)
This study aims to analyze the need for developing local-potential-based entrepreneurial credentials in Vocational High Schools (SMK) in Palangka Raya City. The main issue raised is the mismatch between entrepreneurship learning in vocational schools and regional economic potential, which has not been systematically accommodated in the form of competency recognition or credentials. The study used a descriptive quantitative approach with a survey design of 265 respondents consisting of teachers, heads of expertise programs, and students from eight public and private vocational schools. The instrument was developed based on the Entrepreneurial Competence Framework (European Commission, 2016) and validated through expert judgment (CVR = 0.87; Cronbach's Alpha = 0.921). The results show that the level of need for entrepreneurial credentials is in the high to very high category (mean = 4.36), with the largest gaps in digital marketing and local-material-based production competencies. Factor analysis resulted in five main dimensions of need: entrepreneurial ideation, local production skills, digital marketing and innovation, microfinance management, and community collaboration, with a total variance of 79.5%. This finding confirms the need to develop a “glocal” entrepreneurial credential model, namely integrating global competencies with local wisdom values ​​to encourage contextual entrepreneurship curriculum design and increase the competitiveness of vocational school graduates based on regional economic potential.